Nitrogen assessment : Pakistan as a case-study - Aziz, Tariq (Academic Press, 2022)
Nitrogen Assessment: Pakistan as a Case-Study provides a detailed overview of issues and challenges related to nitrogen use and overuse, thus serving as a reference for researchers in Pakistan and providing important insights for other geographic regions. Excess and inefficient nitrogen use in crops and livestock sectors is polluting our rivers, seas, atmosphere, and ecosystems, contributing to climate change, hampering biodiversity, and contributing to stratospheric ozone depletion. This book covers the importance of nitrogen in relation to food security, human health, and economic stability in South Asia. It also discusses nitrogen status, sources, sinks, and drivers of nitrogen use in Pakistan, focusing on current nitrogen measures and policies. Nitrogen pollution is one of the biggest challenges of 21st Century, and the international scientific community is beginning to recognize the significance of nitrogen pollution and to explore how to combat it.